2011
DOI: 10.1016/j.ejphar.2010.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine/nutrition interaction in the rat brain: Influence on latent inhibition and cortical spreading depression

Abstract: Caffeine, like malnutrition, can produce behavioral and electrophysiological alterations. However, the interaction of both factors remains unclear. Here this interaction has been studied in male Wistar rats previously malnourished during the lactation period by feeding their dams the "regional basic diet" of Northeast Brazil, containing about 8% protein, predominantly from vegetable sources (RBD(8)). At 70-75days of life, a subset of the pups was treated intraperitoneally with 30mg/kg caffeine for 4days while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
6
0
4
Order By: Relevance
“…Although the RBD, enriched in carbohydrate and with low protein, has been used in several studies to induce malnutrition [27,28], our study is the first to evaluate a dual hit of RBD-induced malnutrition and osmotic diarrhea, along with the role of zinc as a gut-trophic nutrient to improve intestinal inflammation, intestinal bacterial translocation, and intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Although the RBD, enriched in carbohydrate and with low protein, has been used in several studies to induce malnutrition [27,28], our study is the first to evaluate a dual hit of RBD-induced malnutrition and osmotic diarrhea, along with the role of zinc as a gut-trophic nutrient to improve intestinal inflammation, intestinal bacterial translocation, and intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…These seemingly conflicting outcomes might be attributable to differences in dosage (namely, 10 vs. 30 mg/kg) and/or learning paradigm chosen (i.e., conditioned taste aversion vs. condition active avoidance) to measure LI. However, interpretation of De Aguiar et al’s study [48] should be cautioned, because conditioned taste aversion was strongly reduced in the caffeine-treated animals regardless of stimulus pre-exposure condition. In the absence of clear learning in the nPE condition, one essentially cannot assess the impact of stimulus pre-exposure, and any conclusion on LI is not warranted [see Figure 3 of 48].…”
Section: Discussionmentioning
confidence: 96%
“…However, interpretation of De Aguiar et al’s study [48] should be cautioned, because conditioned taste aversion was strongly reduced in the caffeine-treated animals regardless of stimulus pre-exposure condition. In the absence of clear learning in the nPE condition, one essentially cannot assess the impact of stimulus pre-exposure, and any conclusion on LI is not warranted [see Figure 3 of 48]. Our data showed that LI was not impaired in st-A 2A R-KO mice – neither in the CTA nor the active avoidance paradigm.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations